2010
DOI: 10.1111/j.1420-9101.2010.01976.x
|View full text |Cite
|
Sign up to set email alerts
|

Large‐brained mammals live longer

Abstract: Many mammals have brains substantially larger than expected for their body size, but the reasons for this remain ambiguous. Enlarged brains are metabolically expensive and require elongated developmental periods, and so natural selection should have favoured their evolution only if they provide counterbalancing advantages. One possible advantage is facilitating the construction of behavioural responses to unusual, novel or complex socio‐ecological challenges. This buffer effect should increase survival rates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
137
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(149 citation statements)
references
References 101 publications
(302 reference statements)
6
137
6
Order By: Relevance
“…In practice, we usually see lower rates of reproduction [70,73], perhaps largely because larger-brained species have heavier neonates [70]. The alternative, a compensatory increase in adult lifespan, is confirmed by many studies [70,74,75]. Consequently, because unavoidable mortality ultimately determines adult lifespan [39], the external conditions (predation, disease, seasonality) must allow for such an increase in adult lifespan.…”
Section: Box 1 How Organisms Pay For Increased Brain Sizementioning
confidence: 99%
“…In practice, we usually see lower rates of reproduction [70,73], perhaps largely because larger-brained species have heavier neonates [70]. The alternative, a compensatory increase in adult lifespan, is confirmed by many studies [70,74,75]. Consequently, because unavoidable mortality ultimately determines adult lifespan [39], the external conditions (predation, disease, seasonality) must allow for such an increase in adult lifespan.…”
Section: Box 1 How Organisms Pay For Increased Brain Sizementioning
confidence: 99%
“…In addition, a number of studies have demonstrated counterbalances to the costs associated with larger RE, including greater lifespan [8] and increased introduction success [10,23]. Perhaps more importantly, studies have found a number of behaviours that correlate with larger RE, such as increased behavioural flexibility [15], social cognition [7], allomaternal care [24], and tool use [9].…”
Section: (A) Relative Encephalization and Risk Of Endangermentmentioning
confidence: 99%
“…Many studies have examined relative encephalization (RE), a measure of brain size after accounting for the effects of body size and phylogeny, and have found that higher RE is correlated with longer lifespan [8], complex social intelligence [9], increased learning capabilities [7], introduction success [10], and a diet more varied in space and time [11]. These studies have found RE to be a biologically relevant measure across a broad array of taxa ranging from reptiles to primates.…”
Section: Introductionmentioning
confidence: 99%
“…Many comparative studies have been aimed at understanding how and why such variation evolved, and have identified a range of factors associated with the evolution of large brains. One general factor robustly correlated with brain size is life history; larger-brained species, such as humans, develop slowly and have extended periods of juvenility and long lifespans, effects that remain after accounting for differences in body size (1)(2)(3)(4)(5)(6)(7)(8). These associations have been interpreted in two different ways.…”
mentioning
confidence: 99%
“…These associations have been interpreted in two different ways. First, life history correlates could reflect the benefits of large brains in providing a "cognitive buffer" against environmental unpredictability, improving survival and permitting long lives (2,6,7). Second, selection on brain size might have secondary consequences for life history because larger brains impose a developmental cost in terms of a need for extended growth and maturation (3)(4)(5)8).…”
mentioning
confidence: 99%